2020
DOI: 10.1038/s41598-020-68028-9
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar transcranial alternating current stimulation in the gamma range applied during the acquisition of a novel motor skill

Abstract: The development of novel strategies to augment motor training success is of great interest for healthy persons and neurological patients. A promising approach is the combination of training with transcranial electric stimulation. However, limited reproducibility and varying effect sizes make further protocol optimization necessary. We tested the effects of a novel cerebellar transcranial alternating current stimulation protocol (tACS) on motor skill learning. Furthermore, we studied underlying mechanisms by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 65 publications
3
29
2
Order By: Relevance
“…Overall, the authors conclude that synchronizing the activity of cortical and cerebellar areas in the gamma frequency band affects explicit motor learning over a wide intervals of time (i.e., 1 day after learning). In a more recent study, 50 Hz left cerebellar tACS did not affect performance in an explicit motor learning task requiring the execution of a grip force to move a cursor [37]. The difference in montage and hand between this study (left cerebellum and non-dominant hand) and our study (right cerebellum and right hand) might account for the divergent results and suggests that the effects depend on the stimulated hemisphere.…”
Section: Discussioncontrasting
confidence: 85%
“…Overall, the authors conclude that synchronizing the activity of cortical and cerebellar areas in the gamma frequency band affects explicit motor learning over a wide intervals of time (i.e., 1 day after learning). In a more recent study, 50 Hz left cerebellar tACS did not affect performance in an explicit motor learning task requiring the execution of a grip force to move a cursor [37]. The difference in montage and hand between this study (left cerebellum and non-dominant hand) and our study (right cerebellum and right hand) might account for the divergent results and suggests that the effects depend on the stimulated hemisphere.…”
Section: Discussioncontrasting
confidence: 85%
“…We suspect that the entrainment at this frequency neither alters the baseline firing rate of these neurons nor recruits further cerebellar neurons to respond to TMS. In support of this, recent work showed that 50Hz cerebellar tACS did not enhance motor skill learning or retention when compared to sham stimulation [63], thus it could be argued that this frequency is suboptimal for facilitating processes that are involved in motor skill learning. Contrary to this, Naro and colleagues found that 50 Hz tACS reduced CBI and improved the performance of a sequential tapping motor task [27].…”
Section: Discussionmentioning
confidence: 95%
“…However, no clear association with behaviour (training gain) was present. It is important to note, that when applying other tasks and stimulation paradigms no effect of training phase 58 or opposite tendencies 59 on SICI move modulation have been reported. In future work, it would be interesting to also study additional aspects of neurotransmission with TMS-based techniques for instance assessing long-interval intercortical inhibition (LICI—GABA B -ergic) or short-latency afferent inhibition (SAI—acetylcholinergic) to disentangle potential other underlying mechanisms of tDCS and motor learning 18 .…”
Section: Discussionmentioning
confidence: 91%